Comparison of Certified Civil Servant Teachers and Uncertified Civil Servant Teachers on the Physical Education Teaching and Learning Process in Public Elementary Schools in Muara Saung District - Alfian Kurniawan; Martiani Martiani; Juwita Juwita (Sinar Sport Journal, 2021)
The effect of certified PNS teachers with non-certified PNS teachers on the learning process. Comparison of physical education learning for certified PNS teachers with non-certified PNS teachers. To know about the teaching and learning process of physical education, certified civil servant teachers and non-certified civil servant teachers in public elementary schools throughout the district of Muara Sahung. The research method in this study used a qualitative descriptive approach in which the research used an analysis of events and phenomena. The research procedure was education learning meetings. Based on the results of the research that has been found, the following conclusions are drawn: PNS teachers of physical education certification always try to improve quality by utilizing all existing facilities in the school. Judging from the results above which are data from the answers to the Questionnaire for PNS Physical Education Teachers Uncertified from a total of 25 questions with 4 kinds of answer choices Always with 18 answers, Often (SR) with 6 answers, Sometimes (KD) 0 with no answers , and Never (TP). While the PNS teacher of physical education certification of a total of 25 questions answered with 4 kinds of answer choices Always (SL) with 23 answers, Often (SR) with 2 answers, Sometimes (KD) 0 answers with no answers, and Never (TP). ) with the answer 1. Meanwhile, non-certified physical education civil servant teachers often try to improve the quality of physical education learning by utilizing all existing facilities in the school. This research is only limited to knowing the comparison of certified physical education civil servant teachers and non-certified physical education civil servants teachers to the physical education learning process. The author realizes that there are many shortcomings and is still far from perfect.